Pengaruh Pembangunan Kepercayaan, Dialog Tatap Muka, Komitmen Proses, Serta Pemahaman Bersama Dan Hasil Awal Terhadap Keberhasilan Tata Kelola Kolaboratif Se Kelurahan Kota Banjarbaru - Destiana, Anindya Risa; Mahyuni, Mahyuni; Samahuddin, Samahuddin; Herawaty, Netty (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the effects of trust building, face-to-face dialogue, commitment to process, and shared understanding with intermediate outcomes on collaborative governance success across all urban villages in Banjarbaru City. This research employs a quantitative explanatory survey design. Data were collected through questionnaires from collaborative actors at the village level and analyzed using multiple linear regression to examine both partial and simultaneous relationships among variables. The results show that trust building has a positive and significant effect on collaborative governance success, indicating that inter-actor trust, transparency, and accountability are key drivers of effective collaboration. Face-to-face dialogue demonstrates a significant negative relationship, suggesting that intensive interactions without clear direction and follow-up may reduce collaborative effectiveness. Commitment to process does not show a significant partial effect, indicating that procedural commitment mainly functions as a supporting mechanism rather than a direct determinant of outcomes. Shared understanding and intermediate outcomes exhibit a significant negative effect, implying that unmanaged preliminary agreements may create excessive expectations and hinder final outcomes. Simultaneously, all variables significantly influence collaborative governance success, confirming that collaborative governance operates as an integrated and dynamic system where relational, communicative, and procedural dimensions interact to shape policy outcomes.